Viabilidade microbiana e propriedades físico-químicas de kefir de água atomizado e liofilizado - Almeida, Klinger Vinícius de (2023)
Water kefir is a sucrose-based non-dairy fermented beverage, with brown sugar being the main substrate. The grains can be reused for subsequent fermentations by transferring them to a new, fresh substrate. The resulting drink is carbonated, cloudy, slightly alcoholic and sweet; its composition is influenced by growing conditions and the microbiota of the grains. This study aimed to develop and analyze the physicalchemical, microbiological and technological characteristics of water kefir powder. The best fermentation conditions observed included the use of 5% grain, 10% brown sugar and an incubation temperature of 25°C. As a result of the metataxonomic analysis carried out on kefir grains and fermented beverage, it was found that the bacterial compositions comprised seven genera, namely: Acetobacter, Gluconobacter, Lactobacillus, Leuconostoc, Oenococcus, Sporolactobacillus and Zymomonas. Within these genera, nine species were identified, 94.31% and 91.68% corresponding to Zymomonas mobilis, for grains and beverages respectively. In relation to fungi, Ascomycota was the only phylum identified, with five genera detected in both the grains and the beverage: Lachancea, Saccharomyces, Torulaspora, Wickerhamomyces and Pichia. Lachancea fermentati corresponded to 95.54% of the grain composition and 67.53% of the fermented beverage composition. The values of the physical and physical chemical analyzes of the atomized and freeze-dried beverage varied in relation to pH (5.24 ± 0.02 to 5.52 ± 0.04), water activity (0.242 ± 0.004 to 0.392 ± 0.024) and humidity (2.68 ± 0.27 to 4.42 ± 0.01), respectively. Powders subjected to the spray drying process showed significant solubility, ranging from 79.09 ± 1.18 to 81.34 ± 1.66, statistically higher (p<0.05) than that of freeze-dried samples. In relation to the hygroscopicity parameter, all powders demonstrated values above 10%, therefore characterizing themselves as hygroscopic. Tests that incorporated inulin as wall material, whether in combination or alone, showed significantly higher hygroscopicity. An increasing trend in the compacted density of the powders was also observed as inulin was incorporated as a wall material. For apparent density, samples containing 100% inulin as wall material, subjected to both spray drying and freeze XV drying, showed higher values (p<0.05) compared to the others. Spray drying, which resulted in a logarithmic reduction of 3 log CFU/g, demonstrated potential to produce powdered water kefir. However, freeze-drying has been shown to be a more effective method than atomization for preserving the viability of microorganisms, making it a potential source of probiotics.